ATD talent development and training in healthcare handbook - Rider, Gregory; Burandt, Jacque; Papavaritis, Niranjani Chidamber (Association for Talent Development, 2022)
Your Guide for Success in Talent Development and Healthcare Within every corner of a healthcare system reside talent development and training initiatives and thus the need for talent development (TD) professionals and expertise. The ATD Talent Development and Training in Healthcare Handbook addresses the many opportunities and complex TD professionals face in the growing and rapidly changing healthcare space. Effective talent development is the thread that weaves through an entire healthcare organization to ensure it is up to standard with latest practices in treating patients while providing a safe and engaging environment for staff. Whether you are new to the field, a clinician new TD, or a seasoned TD professional in need of solutions and best practices, you can turn to this evergreen resource whenever you need tried-and-true advice. TD professionals have the unique role of tying together organizational and employee advancement in healthcare systems--and likewise, this handbook dives into areas for both business and professional evolution. It covers six key themes across 26 chapters: Learning and Development Basics Organizational Development Employee Development Business Acumen for the Health System Digital Transformation and Literacy Patient-Centric Care Written by 25 fellow healthcare practitioners with extensive experience in the field--from nurses, physicians, and administrators to instructional designers, chief learning officers, technology experts, and leaders across the industry--this book will help you maximize the impact of your work and improve your abilities to deliver the best care possible to your patients.